Enhanced circular parasitic element at directional wideband wearable antenna for microwave breast imaging applications - Koma'rudin, Nur' Atika; Salim, Norhuda; Zakaria, Zahriladha; Hassan, Nornikman; Ping Jack, Soh (2024)
A 3.06 GHz and 7.0 GHz wideband wearable antenna for microwave imaging (MWI) in breast cancer applications has been developed, involving design, simulation, fabrication, and measurement. Simulations for Antenna A, Antenna B, and Antenna C were conducted using CST Microwave Studio. The wearable antenna is intended for MWI breast cancer diagnosis. A hemisphere breast phantom with three fat layers, a round tumor, and skin (thicknesses of 68 mm, 5 mm, and 2 mm) was created and measured. Data from the breast phantom was analyzed using a modified delay and sum (mDAS) imaging technique in MATLAB to identify the tumor's location. For simulation of Antenna C, it shows the resonances at 3.07 GHz and 5.15 GHz with - 37.15 dB and - 38.51 dB, respectively. For measurement, it stated that a 3.29 GHz, 5.51 GHz, and 6.67 GHz, with return losses of - 24.67 dB, - 17.65 dB, and - 19.62 dB, respectively.